2001
DOI: 10.1177/107110070102200404
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Posterior Tibial Tendon Dysfunction on Hindfoot Kinematics

Abstract: This biomechanical study investigated the functional role of the posterior tibial tendon (PTT) in acquired flatfoot mechanics. Acquired flatfoot deformity has been attributed to PTT dysfunction; however, the progression from acute dysfunction to end-stage deformity has not been fully demonstrated. Eight human cadaver lower leg and foot specimens were used in two phases of experimental testing. In Phase 1, intact (normal) specimens were loaded to simulate (a) heel strike, (b) stance, and (c) heel rise both with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
60
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 41 publications
4
60
1
Order By: Relevance
“…1), 5,22 which applied compressive forces to the tibia and fibula and tensile forces to the tendons. The frame was made of acrylic to minimize interference with the Fastrak 3D electromagnetic motion tracking system (Polhemus, Colchester, VT).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…1), 5,22 which applied compressive forces to the tibia and fibula and tensile forces to the tendons. The frame was made of acrylic to minimize interference with the Fastrak 3D electromagnetic motion tracking system (Polhemus, Colchester, VT).…”
Section: Methodsmentioning
confidence: 99%
“…20 Attenuation of ligaments and tendons followed by cyclic axial loading has been used to simulate progressive development of soft tissue laxity. 5,16,21 Deland et al 20 recently reported MRI data showing which ligaments become attenuated in adult acquired flatfoot. The involved ligaments are the superomedial and inferomedial calcaneonavicular, talocalcaneal interosseous, plantar naviculocuneiform, plantar first metatarsocuneiform, and anterior superficial deltoid ligaments.…”
mentioning
confidence: 99%
See 3 more Smart Citations